Implementasi Discovery Learning Berbantuan Kahoot! Untuk Meningkatkan Keaktifan Belajar Peserta Didik Pada Pembelajaran Matematika - Aisyah Ramadhani; Suparni; Sumbaji Putranto; Nur Harsih Setyowati (J-SES : Journal of Science, Education and Studies, 2026)
This study aims to analyze the implementation of the discovery learning (DL) model assisted by the Kahoot! application to improve students' active learning in mathematics. The primary issue addressed was the low level of student engagement, which was initially recorded at only 20%. This study employed a qualitative descriptive approach using Classroom Action Research (CAR) consisting of two cycles. The subjects were 29 students of class XI H at MAN 2 Yogyakarta during the odd semester of the 2025/2026 academic year. Data were collected through observation, interviews, and documentation. The results indicated that the strategic integration of Kahoot! into key phases of Discovery Learning successfully increased student activity significantly to 98%. This synergy strengthened mental engagement through the self-discovery process while boosting intrinsic motivation through gamification elements. It is concluded that the implementation of Discovery Learning assisted by Kahoot! effectively improves students' active participation in mathematics learning.